An Analysis Of Sports Learning In The Sports Giftedness School Of Bengkulu Province - Feby Elra Perdima; Ajis Sumantri (Penerbit Jurnal Indonesia, 2023)
Developing sports achievements requires a forum or organization, and is supported by training activities, quality coaches, facilities and infrastructure. This research aims: (1) to determine the quality of coaches possessed by sepak takraw coaches at SKO. (2) to find out the implementation of the sepak takraw sports training program at SKO. (3) to find out the organizational mechanism of sepak takraw at SKO. (4) to find out the completeness of the facilities and infrastructure available to support the sepak takraw sport performance development program at SKO. The population in this study used total sampling because all respondents in the SKO sepak takraw management were all taken as research objects consisting of 18 athletes, coaches, sepak takraw administrators. The variable used in this research is coaching performance in sepak takraw sport. Data collection methods use questionnaires and documentation. The data collected was analyzed using descriptive percentage analysis techniques. The research results show that the quality of athletes based on descriptive analysis is included in the good criteria with a percentage of 41,7% the quality of coaches based on descriptive analysis is included in the poor criteria with a percentage of 67%.